2015
DOI: 10.1371/journal.pone.0120379
|View full text |Cite
|
Sign up to set email alerts
|

Dilemma of Dilemmas: How Collective and Individual Perspectives Can Clarify the Size Dilemma in Voluntary Linear Public Goods Dilemmas

Abstract: Empirical findings on public goods dilemmas indicate an unresolved dilemma: that increasing size—the number of people in the dilemma—sometimes increases, decreases, or does not influence cooperation. We clarify this dilemma by first classifying public goods dilemma properties that specify individual outcomes as individual properties (e.g., Marginal Per Capita Return) and group outcomes as group properties (e.g., public good multiplier), mathematically showing how only one set of properties can remain constant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
1
11
1
Order By: Relevance
“…Partially supporting Hypothesis 1a, when temptation increased with group size, 20-person groups cooperated significantly less than 4-person groups, yet surprisingly, 40-person and 4-person groups did not vary in cooperation. Unexpectedly, inconsistent with previous research (Barcelo and Capraro, 2015;Shank et al, 2015), we found no statistical difference in cooperation across groups of 4, 20, and 40 when gain increased with group size (i.e., fixed MPCR). Thus, keeping the MPCR fixed may buffer against potential negative consequences of larger groups for cooperation and collective action.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Partially supporting Hypothesis 1a, when temptation increased with group size, 20-person groups cooperated significantly less than 4-person groups, yet surprisingly, 40-person and 4-person groups did not vary in cooperation. Unexpectedly, inconsistent with previous research (Barcelo and Capraro, 2015;Shank et al, 2015), we found no statistical difference in cooperation across groups of 4, 20, and 40 when gain increased with group size (i.e., fixed MPCR). Thus, keeping the MPCR fixed may buffer against potential negative consequences of larger groups for cooperation and collective action.…”
Section: Discussioncontrasting
confidence: 99%
“…Specifically, when the group payoff (MGR) is fixed, gain remains constant but temptation increases with group size, such that the personal benefit from cooperation decreases in larger groups. In contrast, when the individual payoff (MPCR) is fixed, larger groups produce greater added benefits when all cooperate (vs. no one cooperates), such that temptation remains constant but gain increases with group size, making cooperation more likely to occur in larger groups (see Isaac et al, 1994;Barcelo and Capraro, 2015;Shank et al, 2015). Thus, people may adjust their cooperation level depending on how temptation and gain shift as a function of the size of the interacting group.…”
Section: Introductionmentioning
confidence: 99%
“…Another potentially important factor in the public goods game is the group size [60,[66][67][68][69][70][71][72][73]. Some properties, such as the pool multiplier m, are properties of the group, and some, such as the marginal per capita return (MPCR), relate to the individual.…”
Section: B Evolution Of Cooperationmentioning
confidence: 99%
“…The MPCR (which we will denote β) is defined as β = m N where N is the group size. Therefore either m or MPCR can be held constant when the group size changes, but not both [73].…”
Section: B Evolution Of Cooperationmentioning
confidence: 99%
See 1 more Smart Citation